Changing collective action: norm-nudges and team decisions - Diekert, Florian; Eymess, Tillmann (AWI discussion paper series, 2021)
We test whether a descriptive norm-nudge is a suitable policy tool to increase cooperation in a social dilemma when decisions are taken by teams, not individuals. 10 Each team in our experiment comes from a different fishing boat at Lake Victoria, Tanzania. The provision of a norm-nudge is randomized across two decision making mechanisms, enabling us to identify experience with egalitarian or hierarchical decision structures, both present at Lake Victoria. The descriptive norm-nudge increases cooperation by 14 and 16 percentage points for egalitarian and hierarchical 15 team decisions, respectively. Captains from boats with hierarchical organization are particularly responsive.